Doped 2D SnS materials derived from liquid metal-solution for tunable optoelectronic devices. Issue 18 (26th April 2022) - Guo, Xiangyang; Wang, Yichao; Elbourne, Aaron; Mazumder, Aishani; Nguyen, Chung Kim; Krishnamurthi, Vaishnavi; Yu, Jerry; Sherrell, Peter C.; Daeneke, Torben; Walia, Sumeet; Li, Yongxiang; Zavabeti, Ali
Abstract : Semiconductor doping using liquid metals. Abstract : Gas–liquid reaction phenomena on liquid-metal solvents can be used to form intriguing 2D materials with large lateral dimensions, where the free energies of formation determine the final product. A vast selection of elements can be incorporated into the liquid metal-based nanostructures, offering a versatile platform for fabricating novel optoelectronic devices. While conventional doping techniques of semiconductors present several challenges for 2D materials. Liquid metals provide a facile route for obtaining doped 2D semiconductors. In this work, we successfully demonstrate that the doping of 2D SnS can be realized in a glove box containing a diluted H2 S gas. Low melting point elements such as Bi and In are alloyed with base liquid Sn in varying concentrations, resulting in the doping of 2D SnS layers incorporating Bi and In sulphides. Optoelectronic properties for photodetectors and piezoelectronics can be fine-tuned through the controlled introduction of selective migration doping. The structural modification of 2D SnS results in a 22.6% enhancement of the d 11 piezoelectric coefficient. In addition, photodetector response times have increased by several orders of magnitude. Doping methods using liquid metals have significantly changed the photodiode and piezoelectric device performances, providing a powerful approach to tune optoelectronic device outputs.